SUBACUTE THYROIDITIS AND ITS CLINICAL CHARACTERISTICS — A RETROSPECTIVE SINGLE CENTER CLINICAL STUDY - Manevska, Nevena; Bozhinovska, Nikolina; Stoilovska Rizova Bojana; Stojanoski, Sinisha; Makazlieva, Tanja (My University, 2022)
INTRODUCTION. Typical clinical features of subacute thyroiditis (SAT) are commonly assessed such as – neck pain and high body temperature, as well as thyroid function abnormalities, elevated inflammatory markers, and strongly suggestive hypoechoic ultrasonography characteristics. Non-steroid anti-inflammatory agents and corticosteroids are used. AIM. To examine the clinical characteristics in patients with SAT, by determining the level of thyroid hormones, the size and structure of the thyroid gland as well as ultrasound and scintigraphy findings. MATERIALS AND METHODS. We performed retrospective analysis in 122 cases of SAT (both genders, mean age 45.05±12,18 years), in the period 2015-2020. We evaluated monthly frequency of the SAT occurrence, the clinical status of the patients including symptoms, body temperature, laboratory results of FT4 and TSH, CRP and ESR level, ultrasonography and scintigraphy findings. RESULTS. Most of the patients complained of neck pain, high body temperature was detected in 66/100 (66%) pts. CRP and ESR Patients were usually diagnosed in hyperthyroid phase of the disease. Enlarged thyroid gland was mostly seen on US, while 52 had normal thyroid gland, with predominantly hypoechoic non-chomogenous structure. Scintigraphy noted “empty” scan (without presentation of functional thyroid tissue) in 72/98 (73,47%) and hypofixation mainly in both lobes in 26/98 (26,53%) pts. CONCLUSION. The awareness of physicians needs to be increased in patients with neck pain for proper diagnosis of SAT, that is often is often misdiagnosed or delayed, leading to erroneous antibiotic overuse. Generally, nonsteroidal anti-inflammatory drugs are effective in reducing thyroid pain in patients with mild cases.
Подострый тиреоидит и его клинические характеристики — ретроспективное одноцентровое клиническое исследование